Development of Electronic Chemotherapy Roadmaps for Pediatric Oncology Patients. (September 2018) - Allen, Steven W.; Hayashi, Robert J.; Jones, Sally J.; Drozda, Mandy H.; Brown, Robert L.; Lackey, Ian T.; Price, Andrea M.; Newland, John M.; Robinson, Deborah L.; Carey, Christina J.; Rich, E. Scott; Huang, Frederick S.
A chemotherapy roadmap is a summary of the chemotherapy plan for a pediatric oncology patient. Chemotherapy roadmaps exist as paper documents for most, if not all, pediatric oncology programs. Paper chemotherapy roadmaps are associated with risks that can negatively affect the safety of the chemotherapy process. This institution explored the feasibility of converting paper chemotherapy roadmaps into an electronic form. The pediatric information systems team developed an innovative computer application that can generate electronic chemotherapy roadmaps, and the pediatric oncology program established a novel workflow that can operationalize them. Electronic chemotherapy roadmaps have been produced for 36 treatment protocols, and 369 electronic chemotherapy roadmaps have been used for 352 pediatric oncology patients. They have functioned as designed and have not had any unintended effects. In the 5 years after their implementation, the average proportion of patient safety events involving paper or electronic chemotherapy roadmaps decreased by 78.7%. This report is the first to demonstrate the feasibility of creating and implementing electronic chemotherapy roadmaps. Continued expansion of the current library will be necessary to formally test the hypothesis that electronic chemotherapy roadmaps can decrease the risks associated with their paper counterparts and increase the safety of the chemotherapy process.